Migrating boulders on the surface of Alpine valley glaciers. Issue 2 (3rd April 2021) - Alean, Jürg; Schwendener, Lea; Zemp, Michael
ABSTRACT: Boulders in the ablation areas of Alpine valley glaciers were found to not travel along with the ice in a passive manner only. Many show an additional but smaller component of movement towards the south. We investigate this phenomenon and its governing processes using field observations and measurements from terrestrial and aerial photographs of glaciers in the Swiss Alps. We found that large boulders can migrate from their medial moraine due to cyclic formation of classical glacier tables and also a similar process that produces ice tails. The main driving factors behind boulder migration are the size (and shape) of the boulder, ablation, radiation, and surface slope. On glaciers roughly oriented to the east or west, these processes result in a sorting of boulders from the supraglacial moraine towards the southern side, i.e. towards the sun. Future studies complementing our approach using a differential global positioning system should be able to better distinguish between the velocity components of ice flow and boulder migration, determine the precise azimuth of the latter, and investigate the potential influence on photogrammetric feature tracking.